Evaluating Patient and Provider Preferences for a Once-Weekly Basal Insulin in Adults with Type 2 Diabetes - Kerr D; Rajpura JR; Namvar T (Patient Preference and Adherence, 2024)
David Kerr,1 Jigar Ramesh Rajpura,2 Tarlan Namvar3 1Center for Health Systems Research, Sutter Health, Santa Barbara, CA, USA; 2Department of US Health Economic and Outcomes Research – Rare Disease Portfolio, Novo Nordisk Inc, Plainsboro, NJ, USA; 3Department of Evidence Synthesis and Value Assessment, Novo Nordisk Inc, Plainsboro, NJ, USACorrespondence: David Kerr, Diabetes Research and Digital Health Equity, Sutter Center for Health Systems Research, Santa Barbara, CA, USA, Tel +1 (805) 624-8688, Email david.kerr@sutterhealth.orgPurpose: The global burden of disease of type 2 diabetes (T2D) is significant, and insulin currently plays a central role in T2D management. This study sought to assess the preferences of patients with T2D and healthcare providers (HCPs) involved in T2D care regarding a hypothetical once-weekly basal insulin in comparison to current basal insulin options.Patients and Methods: In a survey-based study in the United States that included a discrete choice experiment (DCE), patients with T2D (insulin naïve and current insulin users) and providers who treat individuals with T2D were asked to evaluate current basal insulins and identify attributes of importance regarding a hypothetical once-weekly basal insulin. A regression analysis was conducted to identify drivers of preference by relevant demographics, attitudes, and behaviors.Results: Most respondents (91% of patients with T2D and 89% of HCPs in the base case scenario) would choose a once-weekly basal insulin product over another type of basal insulin. Both patients with T2D and HCPs rated insulin type and delivery method to be attributes of highest importance in the discrete choice exercise. Current basal insulin users (“insulin experienced”) reported higher levels of confidence that a once-weekly insulin would help them to achieve their desired blood sugar levels compared to their current basal insulin (5.7 vs 5.2 on a 7-point Likert scale). Most insulin-experienced respondents (88%) were likely to inquire about once-weekly basal insulin, and most HCPs (85%) indicated willingness to educate patients on management of their T2D using a once-weekly basal insulin.Conclusion: Discussing preferences for T2D medication management is important for patients and HCPs to ensure treatments are offered for patients based on their preferences. This study showed that patient and provider preferences are similar towards a once-weekly basal insulin over current basal insulin preparations.Plain Language Summary: Type 2 diabetes (T2D) is a medical condition where the body has difficulty managing insulin, a hormone used to control glucose, or sugar, that is broken down in the bloodstream. Many people with T2D have to take insulin to help their bodies manage their blood sugar effectively. We aimed to find out what people with T2D and healthcare providers (HCPs) think about a new type of basal insulin that only needs to be taken once a week, as compared to current basal insulins that are taken every day. We found that most people with T2D (91%) and HCPs (89%) would prefer a once-weekly insulin rather than another type of basal insulin. People with T2D currently taking insulin were also more confident that a once-weekly insulin could help control their blood sugar. Many people who are already using basal insulin (88%) said they would ask their HCP about a once-weekly insulin. HCPs said they were willing to educate patients about a once-weekly insulin (85%). This study shows that it is important for people with T2D and their HCPs to discuss what type of insulin is best for them, including the type of insulin and how often it is taken. Sharing preferences about medication options may be helpful in reducing the overall impact of the condition. Keywords: diabetes mellitus, type 2, insulin, long-acting, surveys and questionnaires, patient preference, provider preference